2020
DOI: 10.1117/1.oe.59.6.064103
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reconstruction quality metric for optical three-dimensional measurement systems in use for hot-state measurement object

Abstract: Optical three-dimensional (3-D) geometry measurements are state of the art when it comes to contactless quality control and maintenance of the shape of technical components that exclude tactile measurements due to filigree or internal structures. Optical inspection methods are also characterized by a fast and high-resolution 3-D inspection of complex geometries. And due to their noncontact principle, they can carry out measurements in places that would otherwise not be accessible due to harsh environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In a previous paper [15], we used redundantly reconstructed 3D points of a multi-camera FPS to estimate the magnitude of the light deflection that was occurring when measuring a red-hot object. There, we concluded that the deviations of redundantly reconstructed points were a valid metric to quantify said effect.…”
Section: Using a Multi-camera Fringe Projection System To Estimate Thmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous paper [15], we used redundantly reconstructed 3D points of a multi-camera FPS to estimate the magnitude of the light deflection that was occurring when measuring a red-hot object. There, we concluded that the deviations of redundantly reconstructed points were a valid metric to quantify said effect.…”
Section: Using a Multi-camera Fringe Projection System To Estimate Thmentioning
confidence: 99%
“…The measurement system followed the concept of multi-camera fringe projection profilometry and was based on the findings of Bräuer-Burchard et al [16] and Reich et al [17]. We explained the calibration and the main functions of the measurement system in a previous paper [15]. The forced air flow actuator consisted of three commercially available nozzles with a minimum inner diameter of d n = 0.8 mm and a custom-made aluminum connection block.…”
Section: Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have used stereo-vision [ 4 , 5 ], light-section [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] or fringe projection profilometry [ 16 ] to acquire geometry data for quality control and wear analysis for hot forging processes. In previous papers, we have presented a method to estimate the influence of refractive index gradients on the results of optical 3D geometry measurements of hot specimen by evaluation of the reconstruction quality [ 17 ]. Additionally, we have discussed the use of a forced air flow similar to the air knife of [ 18 ] to compensate the light deflection effect when measuring the 3D geometry of red-hot specimens [ 19 ].…”
Section: Introductionmentioning
confidence: 99%